Unit tests & benchmarking - Reyelts, Toby.; Safari eBooks; Voices That Matter Conference ([United States?] : Addison-Wesley, 2007)
"We all want to be able to deliver reliable applications to our customers, but how can we do that in the face of Ajax? Each browser has its own unique bugs, quirks, and performance characteristics. Learn how GWT's unique support for JUnit can help you squash bugs before they make it to your users. This session covers the entire gamut of testing, from basic test writing and execution, to asynchronous testing, and parallel remote web execution. Additionally, we'll tackle the use of benchmarking to improve your application performance, prevent regressions, and identify insidious performance problems in browsers."--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from title frames.
"Voices that matter, the technology conference series from the publishing imprints of Pearson Education."
Electronic reproduction.
Keywords: Google Web Toolkit; Ajax (Web site development technology); Application software; Electronic books